The relationship between dishonest academic behaviour and students' attitudes towards school offences - Tovarović Jelena; Stevanović Nikola (Psihološka Istraživanja, 2023)
The aim of this study is to determine the relationship between academic dishonesty and students' attitudes towards school offences. The research included 347 respondents from primary (the seventh and eighth grades) and secondary (the second and third grades) schools in the Republic of Serbia. The Measurement of Dishonest Behaviour (MDB) was used to assess several types of dishonest behaviour, while the School Offences Scale (SOS) was used to evaluate the attitudes towards school offences. According to the findings, there is a significant positive relationship between dishonest behaviour and students' attitudes towards school offences. The total score of students' attitudes has the highest relationship with the subscale of dishonest behaviour connected to Deception, while the total score of dishonest behaviour has the highest correlation with the subscale Playing Truant. Additionally, there are significant differences regarding cheating in schools between the younger and older students; it was observed that the older students had higher scores on both scales. The findings of canonical correlation analysis, which focused on the relationship between the sets of behavioural scales and attitudinal scales, are also discussed. Additionally, the relationships between the attitudes towards school offence and dishonest behaviour are explained through the Theory of Planned Behaviour, while possible instructions for predicting dishonest behaviours, reducing absenteeism from classes, and other methods of reducing cheating, are outlined in the conclusion.